Disquiet, please! more humor writing from The New Yorker - Remnick, David; Finder, Henry (Random House, 2008)
A compendium of literary humor from the pages of "The New Yorker" features essays and articles by S.J. Perelman, Dorothy Parker, Calvin Trillin, Garrison Keillor, Steve Martin, David Sedaris, and Ian Frazier